Lymphatic Transport Efficiency Determines Metastatic Potential of Cutaneous Melanoma - Holder, Ashley M.; Ziemys, Arturas (Frontiers in Oncology, 2020)
Background: In staging patients with clinical stage I-II melanoma, the sentinel lymph node (SLN) is the most important prognostic indicator; however, the false negative rate of SLN biopsy (SLNB) is 15%. Methods: Nine patients with clinical Stage I-II melanoma underwent SLNB with repeated intraoperative radiotracer measurements to determine lymphatic transport efficiency (LTE), which was correlated with clinicopathologic data. Results: LTE demonstrated excellent prediction of SLN status. LTE in patients with occult nodal metastasis is 50 times faster than those with negative SLNBs. There was no confounding of LTE by clinicopathologic factors. Significance: LTE is a novel biomarker for metastasis, with transformative potential for personalized precision diagnostics of early-stage disease and improved patient survival.